Incremento de las Cuentas por Cobrar de la "Cooperativa de Ahorro y Crédito Salitre" Sucursal Balzar - Daniel Steven Martínez Álava, Daniel Steven Martínez Álava (2018)
This case study investigates the increase in accounts receivable from the Savings and Credit Cooperative "Salitre" Ltda. Balzar Branch, in said institution He noted that there is a problem that affects it since 2015 when within its states financials showed an increase of 72.87% compared to 2014, said increase depended on the criminal act committed by the employees of the agency that They took advantage of the trust placed in them by managers and the lack of internal control, in falsifying information and altering the accounting records of accounts by charge to commit an embezzlement that generated loss of prestige before the members of the cooperative and the community in general The case was made prior to obtaining the title of Accounting Engineer and Audit under the line of investigation of Accounting Information Management according to the patterns of exploratory research (qualitative type), with interviews becoming the main source of primary information; which were analyzed and supported with bibliographic information and advice from experts in the field. The problem that the institution currently faces was identified; supported on analysis tools to be able to determine the respective conclusions